Neuroanatomical and neurochemical effects of prolonged social isolation in adult mice - Vibol Heng; Michael Zigmond; Richard Jay Smeyne (Frontiers Media S.A., 2023)
IntroductionAs social animals, our health depends in part on interactions with other human beings. Yet millions suffer from chronic social isolation, including those in nursing/assisted living facilities, people experiencing chronic loneliness as well as those in enforced isolation within our criminal justice system. While many historical studies have examined the effects of early isolation on the brain, few have examined its effects when this condition begins in adulthood. Here, we developed a model of adult isolation using mice (C57BL/6J) born and raised in an enriched environment.MethodsFrom birth until 4 months of age C57BL/6J mice were raised in an enriched environment and then maintained in that environment or moved to social isolation for 1 or 3 months. We then examined neuronal structure and catecholamine and brain derived neurotrophic factor (BDNF) levels from different regions of the brain, comparing animals from social isolation to enriched environment controls.ResultsWe found significant changes in neuronal volume, dendritic length, neuronal complexity, and spine density that were dependent on brain region, sex, and duration of the isolation. Isolation also altered dopamine in the striatum and serotonin levels in the forebrain in a sex-dependent manner, and also reduced levels of BDNF in the motor cortex and hippocampus of male but not female mice.ConclusionThese studies show that isolation that begins in adulthood imparts a significant change on the homeostasis of brain structure and chemistry.